Online radicalization: Profile and risk analysis of individuals convicted of extremist offences - Kenyon, Jonathan (Legal and criminological psychology, 2023)
Purpose This study explores socio-demographic profiles and offence histories of 235 individuals convicted of extremist offences in England and Wales who have shown different levels of Internet engagement in their pathway towards radicalization. Methods A comprehensive database of those convicted of extremist offences was developed by reviewing and coding content of specialist Structured Risk Guidance (SRG) and Extremism Risk Guidance (ERG22+) assessment reports, authored by professionals with access to a range of restricted information sources and direct contact with the individual concerned. This enabled a comparison of socio-demographic profiles and offence histories for those who radicalized online, those who radicalized offline and those exposed to both online and offline influences. The analyses further integrated formal risk assessments contained in the reports. Results Findings show a comparatively small prevalence of exclusive online radicalization, but some online influence for the majority of all cases. Pronounced variations in the socio-demographic profiles and offence histories for members of each radicalization pathway group were found. In addition, convicted extremists who radicalized online are assessed as having the lowest overall level of engagement with an extremist group or cause, along with the lowest levels of intent and capability to commit violent extremist acts. Conclusions Gaining a better understanding of the prevalence of online radicalization, and the profiles associated with it, informs the debate on whether extremist content and activities online influence violent extremist behaviour offline and helps to guide counter-terrorism approaches and future policy in this area.